Counter Hegemony Online Media Reporting on Marginalized Religious Groups: A Case Study of the Serikat Jurnalis Untuk Keberagaman (Sejuk) - Anggraini, Maya; Utari, Prahastiwi; Satyawan, Ignatius Agung (UI Scholars Hub, 2023)
The media ecosystem in Indonesia still does not provide a safe space for marginalized religious groups. Information on marginal religious groups is commodified so that these groups are only used as objects, not news subjects who can tell their point of view. Serikat Jurnalis Untuk Keberagaman (Sejuk) seeks to combat this hegemony by advocating journalists regarding coverage of marginalized religious groups. The theory used is the Counter Hegemony Theory and the Concept of Disinformation Capitalism. The research method was descriptive qualitative with a single case study type. Data collection techniques were carried out using semi-structured interviews and the use of literature. the analysis and validity of the data in this study used triangulation techniques. the analysis was performed by data reduction and data grouping to conclude. The result of the research was that the commodification of information occurred because positive information on reporting of marginal religious groups does not generate profits, so that information is limited and not reported. The information, in this case, is political and inaccurate, which means that positive information related to the harmonious practices of marginal religious groups is overshadowed by information related to conflicts and threats against these groups. Sejuk's efforts as an organic intellectual group against media hegemony has changed the perspective of journalists in covering marginal religious groups. Journalists, who have been in contact with and received Sejuk training might write stories that do not stigmatize this group. Even so, there are challenges in the practice of Sejuk, namely the resistance to Sejuk is quite large due to increasingly intense advocacy.